The Effect Of Green Accounting, Corporate Social Responsibility, And Enviromental Social Governance On Company Profitability - Urba Lista, Wa Ode Muhfi; Wulandari, Ika (E-Jurnal Akuntansi, 2024)
This study is intended to examine the effect of Green Accounting, Corporate Social Responsibility (CSR), and Environmental Social Governance (ESG) on the profitability of mining companies listed on the Indonesia Stock Exchange (IDX) for 2020-2023. The study uses a quantitative method with secondary data obtained from the official IDX website. The data analysis technique uses multiple linear regression. Sampling uses a purposive sampling technique, so that a sample of 13 companies was obtained from a total population of 94 companies. The research findings show that Green Accounting has a positive and significant effect on the profitability of mining companies. However, CSR and ESG do not have a significant effect on the profitability of mining sector companies. This study is based on differences in previous research findings and the dynamics of declining profitability in recent years. The novelty of the study lies in the newer observation period and the observation period of 4 years, the use of ESG variables, and the measurement of profitability with ROE. This study provides insight into the role of Green Accounting in increasing profitability and the contribution of CSR and ESG.